JAJANAN PASAR DEMOCRACY - Wargaslot, Rahma (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2017)
ABSTRACTThe value of democracy in the context of food systems reflects equality in food choices, availability of information, sustainability, engagement, and higher levels of satisfaction. In reality, the development of the street food industry tends to steer people away from the concept of democracy. Vendors barely play a role in the food supply chain because their roles have been replaced by advanced food producers. Their important role in the food system has been replaced by other sectors within the industrial food system, such as large supermarkets and food retailers. This means that equal rights as a concept of democracy have been restricted. This essay illustrates a comparison between two major food provision locations, namely large supermarkets. This essay examines the concept of jajanan pasar and democracy in both locations and provides further exploration of how the implementation of